New approaches for quantifying carotenoids content in cassava roots - Sánchez, T.; Morante, N.; Ceballos, H.; Franco, J.; Kulakow, Peter A.; Maroya, N.; Felde, T. um (International Society for Tropical Root Crops, 2012)
Cassava is an ideal vehicle for delivering provitamin A carotenoids to human populations affected by deficiency of this important micronutrient. Rapid cycling recurrent selection has proven to be very effective increasing carotenoids levels in cassava. The maximum level of total carotenoids increased by about 3 μg / g of fresh root each year. As breeding populations evolve large populations are developed and the selection among them becomes increasingly difficult because most genotypes show intense yellow coloration in their roots. Reflectance colorimeter and NIRS were evaluated as potentially useful alternatives to select those roots that will be analyzed through spectrophotometer and/or HPLC. Results indicate that both equipments can help in the selection process.